Spatial Distribution of Heavy Element in Erbil's Municipal Landfills by Using GIS - Sayran Yousif Jalal; Dalshad Azeez Darwesh (Baghdad Science Journal, 2024)
Untreated municipal solid waste (MSW) release onto land is prevalent in developing countries. To reduce the high levels of harmful components in polluted soils, a proper evaluation of heavy metal concentrations in Erbil's Kani Qrzhala dump between August 2021 and February 2022 is required. The purpose of this research was to examine the impact of improper solid waste disposal on soil properties within a landfill by assessing the risks of contamination for eight heavy elements in two separate layers of the soil by using geoaccumulation index (I-geo) and pollution load index (PLI) supported. The ArcGIS software was employed to map the spatial distribution of heavy element pollution and potential ecological risks. The I-geo values in summer varied from -1.700 to 3.560 for Zn, 5.045 to 8.175 for Cd, 2.318 to 4.329 for Pb, 0 to 3.374 for Mn, 1.439 to 3.880 for Ni, 0.638 to 2.278 for Cu, -0.541 to 2.665 for Cr, and -2.495 to 0.778 for Hg. Based on the I-geo categorization, the contamination levels of Zn, Cd, Pb, Mn, Ni, Cu, and Hg ranged from uncontaminated to extremely contaminated. However, all metals were assessed as uncontaminated throughout winter, except I-geo (Cd) and I- geo (Ni) varied from -0.467 to 3.966 and -5.720 to 2.015 were classified from as uncontaminated to strong and uncontaminated to moderately/strongly contaminated respectively. According to the PLI category, most samples were rated as "highly polluted" during summer, but during the rainy season, all samples were rated as "unpolluted".